Hydrogen oxidation electrocatalysts for anion-exchange membrane fuel cells: activity descriptors, stability regulation, and perspectives - Ren, Jin-Tao; Chen, Lei; Wang, Hao-Yu; Feng, Yi; Yuan, Zhong-Yong (Energy & environmental science, 2024)
The burgeoning field of anion-exchange membrane fuel cells (AEMFCs) presents a promising avenue to circumvent the reliance on scarce and costly Pt-based catalysts, offering a zero-carbon emission alternative. Despite the success of numerous noble metal-free cathodic oxygen reduction reaction catalysts in AEMFCs, the sluggish kinetics of the anodic hydrogen oxidation reaction (HOR) in alkaline media, necessitating a high Pt amount, poses a substantial impediment to AEMFC development. This review delves into the intricate landscape of the alkaline HOR, commencing with exploration of prevailing theories grounded in diverse activity descriptors, such as the hydrogen binding energy theory and bifunctional theory. The elucidation of sluggish kinetics and reaction mechanisms in alkaline electrolytes serves as the foundation for the analysis of noble and non-noble metal catalysts, encompassing considerations of morphology, composition, local structure, heterostructure, spillover effects, single atomic catalysts, and oxyphilic site engineering. Emphasis is placed on addressing pivotal but often overlooked challenges, including long-term stability, antioxidation ability, and CO tolerance of HOR catalysts. This review underscores the significance of theoretical investigations and in situ characterization technologies. Subsequently, recent strides in AEMFCs, leveraging various electrocatalysts for enhanced activity and durability, are meticulously summarized. The narrative concludes by spotlighting persisting controversies surrounding alkaline HOR mechanisms, along with an exposition of challenges and prospective research directions vital for the eventual commercialization of AEMFCs. The general principles in terms of reactivity and stability to design efficient electrocatalysts for the alkaline hydrogen oxidation reaction are reviewed. The performance of catalysts in anion-exchange membrane fuel cells is further discussed.